Fullmetal alchemist. 07 - Arakawa, Hiromu, 1973- (Viz Graphic Novel. #7, 2006)
A group of outcasts is determined to discover the alchemical secrets of Alphonse Elric's creation. Now, Ed must go into the Devil's Nest to rescue his brother and face an artificial human being called a homunculus.